NarxCare Scores Greater Than 300 Are Associated with Adverse Outcomes After Primary THA. Issue 9 (September 2021) - Emara, Ahmed K.; Grits, Daniel; Klika, Alison K.; Molloy, Robert M.; Krebs, Viktor E.; Barsoum, Wael K.; Higuera-Rueda, Carlos; Piuzzi, Nicolas S.
Abstract: Background: The association between preoperative prescription drug use (narcotics, sedatives, and stimulants) and complications and/or greater healthcare utilization (length of stay, discharge disposition, readmission, emergency department visits, and reoperation) after total joint arthroplasty has been established but not well quantified. The NarxCare score (NCS) is a weighted scalar measure of overall prescription opioid, sedative, and stimulant use. Higher scores reflect riskier drug-use patterns, which are calculated based on (1) the number of prescribing providers, (2) the number of dispensing pharmacies, (3) milligram equivalence doses, (4) coprescribed potentiating drugs, and (5) overlapping prescription days. The aforementioned factors have not been incorporated into association measures between preoperative prescription drug use and adverse events after THA. In addition, the utility of the NCS as a scalar measure in predicting post-THA complications has not been explored. Questions/purposes: (1) Is the NarxCare score (NCS) associated with 90-day readmission, reoperation, emergency department visits, length of stay, and discharge disposition after primary THA; and are there NCS thresholds associated with a higher risk for those adverse outcomes if such an association exists? (2) Is there an association between the type of preoperative active drug prescription and the aforementioned outcomes? Methods: Of 3040 primary unilateral THAs performed between November 2018 and December 2019, 92% (2787) had complete baseline information and were subsequently included. The cohort with missing baseline information (NCS or demographic/racial determinants; 8%) had similar BMI distribution but slightly younger age and a lower Charlson Comorbidity Index (CCI). Outcomes in this retrospective study of a longitudinally maintained institutional database included 90-day readmissions (all-cause, procedure, and nonprocedure-related), reoperations, 90-day emergency department (ED) visits, prolonged length of stay (> 2 days), and discharge disposition (home or nonhome). The association between the NCS category and THA outcomes was analyzed through multivariable regression analyses and a confirmatory propensity score–matched comparison based on age, gender, race, BMI, smoking status, CCI, insurance status, preoperative diagnosis, and surgical approach, which removed significant differences at baseline. A similar regression model was constructed to evaluate the association between the type of preoperative active drug prescription (opioids, sedatives, and stimulants) and adverse outcomes after THA. Results: After controlling for potentially confounding variables like age, gender, race, BMI, smoking status, CCI, insurance status, preoperative diagnosis, and surgical approach, an NCS of 300 to 399 was associated with a higher odds of 90-day all-cause readmission (odds ratio 2.0 [95% confidence interval 1.1 to 3.3]; p = 0.02), procedure-related readmission (OR 3.3 [95% CI 1.4 to 7.9]; p = 0.006), length of stay > 2 days (OR 2.2 [95% CI 1.5 to 3.2]; p < 0.001), and nonhome discharge (OR 2.0 [95% CI 1.3 to 3.1]; p = 0.002). A score of 400 to 499 demonstrated a similar pattern, in addition to a higher odds of 90-day emergency department visits (OR 2.2 [95% CI 1.2 to 3.9]; p = 0.01). After controlling for potentially confounding variables like age, gender, race, BMI, smoking status, CCI, insurance status, preoperative diagnosis, and surgical approach, we found no clinically important association between an active opioid prescription and 90-day all-cause readmission (OR 1.002 [95% CI 1.001 to 1.004]; p = 0.05), procedure-related readmission (OR 1.003 [95% CI 1.001 to 1.006]; p = 0.02), length of stay > 2 days (OR 1.003 [95% CI 1.002 to 1.005]; p < 0.001), or nonhome discharge (OR 1.002 [95% CI 1.001 to 1.003]; p = 0.019); the large size of the database allowed us to find statistical associations, but the effect sizes are so small that the finding is unlikely to be clinically meaningful. A similarly small association that is unlikely to be clinically important was found between active sedative use and 90-day ED visits (OR 1.002 [95% CI 1.001 to 1.004]; p = 0.02). Conclusion: Preoperative prescription drug use, as reflected by higher NCSs, has a dose-response association with adverse outcomes after THA. Surgeons may use the preoperative NCS to initiate and guide a patient-centered discussion regarding possible postoperative risks associated with prescription drug-use patterns (sedatives, opioids, or stimulants). An interdisciplinary approach can then be initiated to mitigate unfavorable patterns of prescription drug use and subsequently lower patient NCSs. However, given its nature and its reflection of drug-use patterns rather than patients' current health status, the NCS does not qualify as a basis for surgical denial or ineligibility. Level of Evidence: Level III, diagnostic study.